EFFECTIVENESS OF MACROMEDIA FLASH-BASED IPS LEARNING MEDIA TO INCREASE MOTIVATION AND LEARNING OUTCOMES OF PRIMARY STUDENTS - Putri Dewi Nurhasana (Institut Pendidikan Indonesia, 2021)
This research aims to determine the effectiveness of Macromedia flash-based social studies learning media to increase elementary school students' motivation and learning outcomes. This type of research uses a quantitative approach with a quasi experimental method with a pre-test and posttest control group design. The population of this study were fourth grade students at Sendangadi Elementary School. Samples were taken using random sampling technique with 2 experimental group classes and 1 control class. The instruments used in this research were observation sheets and test question sheets. Data analysis used the MANOVA test with the Hotellings Trace formula with a significance level of 5%. The difference in the significance value of the Hotellings Trace test is 0.000 <0.05 for the different test between the experimental group and the control group. Thus, macromedia flash-based social studies learning media is effective in increasing the motivation and learning outcomes of fourth grade elementary school students.